2022
DOI: 10.3390/nu15010197
|View full text |Cite
|
Sign up to set email alerts
|

Lysine or Threonine Deficiency Decreases Body Weight Gain in Growing Rats despite an Increase in Food Intake without Increasing Energy Expenditure in Response to FGF21

Abstract: The objective of this study is to evaluate the effects of a strictly essential amino acid (lysine or threonine; EAA) deficiency on energy metabolism in growing rats. Rats were fed for three weeks severely (15% and 25% of recommendation), moderately (40% and 60%), and adequate (75% and 100%) lysine or threonine-deficient diets. Food intake and body weight were measured daily and indirect calorimetry was performed the week three. At the end of the experimentation, body composition, gene expression, and biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The effect of lysine depletion on body composition in vivo is also controversial. In rats, lysine depletion can reduce body weight, fat mass, and lean mass [2,31]. Interestingly, pigs fed a lysine-depletion diet demonstrated a lower relative proportion of lean components; however, higher carcass fatty components were obtained, together with increased lipogenic genes [32].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of lysine depletion on body composition in vivo is also controversial. In rats, lysine depletion can reduce body weight, fat mass, and lean mass [2,31]. Interestingly, pigs fed a lysine-depletion diet demonstrated a lower relative proportion of lean components; however, higher carcass fatty components were obtained, together with increased lipogenic genes [32].…”
Section: Discussionmentioning
confidence: 99%
“…Lysine is an essential amino acid known for positive nitrogen balance in the human body through its abundance in different human proteins [15]. Lysine deficiency results in a decrease in body weight gain [16]. A lysine-deficient diet reduces growth and bone metabolism, which impacts calcium intestinal absorption and collagen synthesis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Threonine is involved in many metabolic processes. One animal study showed that when threonine was deficient, rats gained less weight and expended less energy [32]. Alanine is an important part of the glucose-alanine cycle.…”
Section: Macrosomia and Amino Acids In Maternal Serummentioning
confidence: 99%